Hormonal responses to concurrent strength and endurance training with different exercise orders - Cadore, E. L.; Izguierdo, M.; dos Santos, M. G.; Martins, J. B.; Rodrigues Lhullier, F. L.; Pinto, R. S.; Silva, R. F.; Kruel, L. F. M. (The Journal of Strength and Conditioning Research, 2012)
The purpose of this study was to examine the influence of the intrasession sequencing of concurrent strength and aerobic training on the acute testosterone (TT) and cortisol (COR) responses. Ten recreationally strength-trained young men (23.5 ± 0.9 years) performed 2 exercise interventions: aerobic-strength (AS) and strength-aerobic (SA), which consisted of 30 minutes of aerobic exercise on a cycle ergometer at 75% of maximal heart rate and 3 sets of 8 repetitions at 75% of 1 repetition maximum (1RM) in 4 strength exercises. Maximal heart rate was determined using a maximal incremental test on a cycle ergometer. Blood samples were collected before, between exercise modalities, and immediately after the concurrent training sessions to determine basal and acute total TT and COR concentrations. There were significant increases in TT after the first modality in both exercise orders (p < 0.05). However, the TT level remained significantly higher than the resting levels after the second exercise modality only in the AS (p < 0.05) which resulted in a significant higher relative total change after the complete concurrent training session compared with SA (p < 0.05). Regarding COR, there were significant increases after the first modality in both AS and SA orders (p < 0.05), but the COR returned to resting levels after the second modality in both AS and SA interventions. During AS and SA, the change observed after the first modality performance was greater than that after the second in both hormones. The present results suggest that the TT response is optimized after the AS order, whereas both AS and SA produced similar hormonal levels at all time points. However, it is important to state that the present results should be applied only when short duration and moderate intensity aerobic training is performed.